Coworking spaces: the relationships between spatial factors with member's collaborative activity and member's satisfaction / Ooi Chia Hoay - Ooi, Chia Hoay (2022)
This paper aims to examine the case study coworking space design towards its users and provide understanding into the relationship between physical space features and its user's satisfaction towards collaboration in coworking space. The study employed direct observation, in-depth interview, questionnaire surveys as methods of data collection in the case study. Analysis of findings demonstrates that physical spatial factors such as openness, variety and flexibility, privacy and distractions, proximity, personalization and territoriality are powerful for influencing user's satisfaction in the coworking space. The finding provides a deeper understanding of the relationship between physical space features of coworking space and its user perceptions of satisfaction in collaboration within the coworking space. The research insights in this study may help architects, interior designers and facility managers in making mindful decisions on the design of coworking space that are more meaningful to the users.